Contribution of coaching in managerial decision making - Andrés Felipe Jiménez-López; María Paulina Vásquez-Varela; Doralba Ramírez Henao (RHS Revista Humanismo y Sociedad, 2020)
The purpose of this paper is to determine the extent of the contribution of coaching in decision making, one of the most sought-after managerial skills in administrative management. Two perspectives are brought into dialogue in this paper. One from organizational coaching, a process leading to positive and lasting changes to pave the way for success in work teams. And the second one from managerial decisions, through the conscious development of skills and resources that allow linking emotions and reason, in the search for alternatives to choose the best option to undertake. This entails qualification of different aspects of the being, the knowing and the doing. While technical knowledge and skills associated to a position are necessary, it is essential to undertake new personal and professional experiences. Here, coaching is a valid option for paving the way for success. Therefore, it is highlighted that coaching effectively contributes, through a deep process of personal transformation, to decision-making, because when higher levels of awareness and internal connection are reached, the ability to fully evaluate situations is expanded, and more assertiveness to choose is achieved, resulting in superior outcomes.